(untitled) (Economic studies journal, 2023)
This study aimed to review the theoretical framework for small and medium enterprises, and unemployment, and also aimed to identify the extent of the contribution of small and medium enterprises in reducing the problem of unemployment in Libya through their contribution to providing work, and to collect the required initial data, a questionnaire form was designed and distributed to the study sample. Represented by the employees of the Sirt for small and medium enterprises, and also resorting to various references and sources to cover the secondary data represented in the theoretical and conceptual framing of the study. Inferential and represented in (T- Test) to analyze hypotheses and obtain results in particular, and after carrying out the necessary analytical procedures and according to the evidence of trends and indicators of the sample’s opinions, the study reached a set of results, the most important of which are: The results proved the validity of the hypothesis that there is a role for small and medium enterprises in reducing unemployment Through the results, we note that small and medium enterprises are The most important in increasing job opportunities for individuals and providing cash in front of daily needs.